STRATEGIC DIRECTIONS OF REFORMS IN THE EDUCATION SYSTEM IN UZBEKISTAN ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
In recent years, in the education system of Uzbekistan there are cardinal changes aimed at the formation of highly qualified personnel in demand in the labor market. In this regard, the country's leadership is taking active actions and measures to reform the education system. The article highlights key changes in the education system of Uzbekistan and the main challenges facing country in the coming years.